The Role of Classical Image Processing Algorithms in the Age of AI Revolution - Gądek-Moszczak Aneta (Technical Transactions)
The article is devoted to the analysis of AI methods used in materials science and, in particular, the possibility of using them in the automatic classification and detection of material structure elements in digital images. The main areas of application of AI algorithms in materials science, such as prediction of material properties, material design, and optimization of technological processes, are presented. Examples of machine learning algorithm applications for classifying structure elements are discussed. Difficulties encountered in implementing AI algorithms in analyzing images of material microstructures were analyzed.